Review of Demotivation in second language acquisition: Insights from Japan; Author: Keita Kikuchi; Publisher: Multilingual Matters, 2015; ISBN: 9781138783093946; Pages: 162 - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2017)
Book review